9x-4=2(8x+4x)+7

Simple and best practice solution for 9x-4=2(8x+4x)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-4=2(8x+4x)+7 equation:


Simplifying
9x + -4 = 2(8x + 4x) + 7

Reorder the terms:
-4 + 9x = 2(8x + 4x) + 7

Combine like terms: 8x + 4x = 12x
-4 + 9x = 2(12x) + 7

Remove parenthesis around (12x)
-4 + 9x = 2 * 12x + 7

Multiply 2 * 12
-4 + 9x = 24x + 7

Reorder the terms:
-4 + 9x = 7 + 24x

Solving
-4 + 9x = 7 + 24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24x' to each side of the equation.
-4 + 9x + -24x = 7 + 24x + -24x

Combine like terms: 9x + -24x = -15x
-4 + -15x = 7 + 24x + -24x

Combine like terms: 24x + -24x = 0
-4 + -15x = 7 + 0
-4 + -15x = 7

Add '4' to each side of the equation.
-4 + 4 + -15x = 7 + 4

Combine like terms: -4 + 4 = 0
0 + -15x = 7 + 4
-15x = 7 + 4

Combine like terms: 7 + 4 = 11
-15x = 11

Divide each side by '-15'.
x = -0.7333333333

Simplifying
x = -0.7333333333

See similar equations:

| 2y^2-y^2=1 | | -7x-4(-2x-18)=80 | | 6x-4(-6x+17)=142 | | -14=-4+5u | | 4x-3(-x-2)=69 | | 2y^2+y=1+y+y^2 | | 5x+2(4x-6)=92 | | 1+-3f=4 | | 7=(3+b)4 | | 6(k-4)-8=9k+7 | | 3-9x=-7(x+5) | | 3x+7(3x-12)=132 | | -1=2w+5 | | 5x+3(x-15)=35 | | 7x+3(7x-6)=150 | | 5x-3(x-5)=-3+4x+14 | | (x+6)=6(x+9) | | 3x+2(7x-6)=73 | | 9x=50000 | | 6x+3(4x-18)=162 | | 8y+12=7x+4 | | 3x+2(x+6)=67 | | 2x-3(4x+5)=-6(x-3)-1 | | y=0.15x+29 | | (5x+12)=180-3x | | 2b-34=54 | | 8=2r-2 | | 2b+3=54 | | 3(2a-6)=8(2a-3) | | 5x-0.1=0.5x-1 | | y-3=.4(x-2) | | 86=4w+10 |

Equations solver categories